Self-Assessment of Health among the Citizens of Serbia in the Transition Period - Natasa Mihailovic; Ivana Simic-Vukomanovic; Marina Luketina-Sunjka; Sandra Zivanovic; Biljana Milicic; Vesna Milicic (Tehran University of Medical Sciences, 2021)
Background: The aim of the research was to compare the differences between the self-assessment of the health in the latest National Health Surveys research and in the one before that. Methods: We used the database of the latest National Health Survey in the Republic of Serbia (2013) and of the one before that (2006), as cross-sectional studies (n=29485). Logistic regression was used to predict the relationship between self-assessment of health and independent predictors. Results: Health condition of the interviewees improved according to their self-assessment. With aging respondents who poorly assessed their health; women assessed their health 1.7 and 1.6 times poorer in the latest research and in the one before that respectively. The odds ratio in patients diagnosed with some disease in the previous 12 months ranged from 2.15 (1.85 - 2.51) to 4.03 (3.22 - 5.05) in the latest research. The strongest predictor was sick leave in the past 12 months with 95% CI = 3.19 (1.87-5.44) in the latest research and 95% CI = 2.27 (1.67-3.08) in the one before that. Conclusion: There was an improvement of the health condition of individuals. Female interviewees, less educated, unemployed, the ones who have some disease and who were on a sick leave rated their health as bad.